OPTIMIZATION OF BLADE DEFLECTION BASED ON HYBRID GENETIC ALGORITHM - WANG YongDing; QIAN YingJuan (Jixie qiangdu)
In order to improve the energy utilization rate of the vertical axis variable angle of attack turbine,a mathematical optimization model of the blade declination angle variation rule was established,using the blade declination angle change with the position angle as the design parameter,the turbine energy utilization rate as the objective function,and genetic algorithm Combined with the method of sequential quadratic programming,the optimization calculation is carried out,and on this basis,the most suitable blade declination variation law is obtained. The deflection angle of the cycloid turbine at different speed ratios is optimized to obtain the optimized declination law. The results show that the energy utilization rate of the hydroturbine is better than that of the original cycloid turbine under the declination law optimized by the hybrid genetic algorithm. The ratio has improved.